Assessing Motivational Factors in Young Serbian Athletes: A Validation Study of the Sport Motivation Scale-II - Damjan Jakšić; Jovana Trbojević Jocić; Marko Manojlović (Psychology in Russia: State of Art, 2024)
Background. Motivation is considered crucial in sports participation and performance, influencing athletes’ psychological well-being, investment in training, and interpersonal relationships. Self-determination theory (SDT) is a prominent framework used to understand motivation in sports, highlighting the importance of autonomous motivation for optimal performance and well-being. A large number of questionnaires for examining processes in sports were created by relying on the constructs of SDT. Objective. This study explores the psychometric characteristics (construct validity) of the Sport Motivation Scale II (SMS-2), as well as gender and age differences in motivation among young Serbian athletes. This questionnaire has proven to be important for understanding the motivation of adult athletes, but so far, its psychometric characteristics have not been sufficiently examined on a sample of young athletes in Serbia. Given the high dropout rate from sports in adolescence, valid questionnaires to assess the motivation of young athletes can help to identify athletes who are at risk of leaving a sport. Design. The sample consisted of 365 young athletes (51% girls, aged 12–16) from Serbia participating in team sports (at an organized level, not a recreational level), including volleyball, basketball, and handball. They completed the SMS-2 using paper and pen, in the presence of a psychologist and with parental consent obtained by the clubs. The questionnaire has been translated into Serbian. Young athletes from team sports were selected due to the large number of adolescents in Serbia who are engaged in organized team sports. There is a small number of adolescents who are involved in organized individual sports. Results. Factor analysis of the SMS-2 revealed six factors, in line with the original structure of the Scale: identified motivation, intrinsic motivation, amotivation, external motivation, integrated motivation, and introjected motivation. The questionnaire demonstrates satisfactory psychometric properties, with Cronbach’s alpha coefficients indicating good internal consistency. Gender differences were obtained only in external motivation, where boys scored higher than girls. No significant differences emerge in motivation across age groups or among athletes participating in different sports. It is possible that differences were not found in relation to the type of sport because there are similarities in the process of working with young athletes in team sports. Conclusion. The Sport Motivation Scale II (SMS-2) showed satisfactory psychometric characteristics in a Serbian sample of young athletes. The original structure was replicated, with six factors representing six types of motivation, in line with SDT. These findings suggest the SMS-2’s validity across gender, age, and sport types, offering a valuable tool for assessing motivation in young athletes engaged in organized team sports.